Export Packaging Training, Export Documents and Export Market Research at MHY Devata Bali Tabanan in Collaboration with Arkansas University - ELFAROSA, Ketut Vini; SINTADEVI, Ni Putu Rita; WIDHIARI, Luh Kemala Putri; LAKSMANA, Nyoman Hendra; RINALDI, Eldian (Akuntansi dan Humaniora: Jurnal Pengabdian Masyarakat, 2024)
MHY Devata Bali is a local business created to accommodate semi-finished products from farmers in Pupuan to Selemadeg Tabanan to be processed, packaged, and marketed. The methods used are surveys, training, and mentoring to adjust the level of understanding and the needs of the solutions offered. The raw materials include coffee, coconut and honey, which produce ground coffee, VCO oil, cooking oil, honey, etc. In its operations, it can market products to local and national markets. It has digital marketing and marketplaces in several places. This has great potential to be developed into an export commodity. For this reason, several requirements must be met according to export standards and requirements that require training and assistance. Because some jobs are still manual, and the company still needs this capability. It is hoped that the company can develop its marketing more widely to the international market to have product advantages and improve the community's welfare, especially local farmers in Tabanan.